Bridging the Knowledge Gap: Towards Establishing the Impact of Leadership Styles on Libyan Small Medium Enterprise Performance (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
SMEs throughout the globe are severely impacted by several challenges that impede the performance ofentrepreneurs. Thus, the purpose of this paper is to identify the impact of leadership style on Libyans’ Small and MediumEnterprises (SMEs) performance. Required data was collected through a random method and a questionnaire administeredon 258 managers of Libyan SMEs. This research suggested that Leaders must invest in training and development in order toadvance their skills and abilities to carry out transformational and transactional leadership styles in their businesses.